Cytaty biblijne w oświeceniowym czasopiśmie "Monitor" = Biblical quotes in "Monitor", the Enlightenment magazine - Gorzelana, Joanna (Zielona Góra: Uniwersytet Zielonogórski, Instytut Filologii Polskiej)
The purpose of this article is to present the functioning of the quotes from the Bible in the "Monitor" magazine in the first decade of its publishing (1765-1774). The phenomenon is interesting because the era of the Enlightenment is commonly associated with the move away from the Church and the fight against religion. However, the longest appearing periodical contains quotations from the Bible (both in Latin and Polish). They are most often cited as the final argument. This shows that the Bible was the indisputable authority for the editors and readers of "Monitor" in the Enlightenment.
Keywords: oświecenie - literatura; Biblia; cytat; "Monitor" - czasopismo; Enlightenment; Bible; quote